POEMS syndrome causing left ventricular hypertrophy, myocardial dysfunction, and pericardial effusion: a case report. Issue 1 (16th December 2021) - Wang, Shanshan; Wu, Xuejie; Li, Hui
Abstract: Background: POEMS syndrome (polyneuropathy, organomegaly, endocrinopathy, M-protein, skin changes) is a paraneoplastic syndrome caused by a plasma cell proliferative disorder. Characteristics of POEMS syndrome include elevated pro-inflammatory and angiogenic cytokine levels that lead to multi-organ dysfunction. Patients have a variety of initial symptoms, but cardiac involvement is not common. Case summary: We report a case of a 31-year-old Chinese woman with chief complaints of chest pain and dyspnoea who was diagnosed with POEMS syndrome. The cardiovascular system in the case study patient was characterized by pericardial effusion, enlarged left atria, abnormal myocardial segmental deformation, left ventricular hypertrophy, pulmonary hypertension, and increased glucose metabolism in the left and right ventricular myocardium. The pericardial effusion diminished, while cardiac function, left ventricular wall thickness, and pulmonary hypertension gradually returned to normal with dexamethasone and bortezomib treatment. Discussion: This case suggests that cardiovascular system damage may be related to systemic diseases. Cardiovascular system damage caused by POEMS syndrome is recoverable after chemotherapy treatment. Echocardiography readily visualizes the changes in the heart of a patient with POEMS syndrome, clearly reflecting the changes in the structure and function of the heart before and after treatment.